Trostbriefe eines mittelalterlichen Herrschers Beileidsbekundungen aus der Innsbrucker Briefsammlung Kaiser Friedrichs II. (und seines Sohnes Konrad IV.) an Angehörige von Verstorbenen - Julian Bitsche (Historia.scribere)
Letters of Consolation from a Medieval Monarch Expressions of Condolences from the Innsbruck Letter Collection of Emperor Frederick II (and His Son Conrad IV) to the Relatives of the Deceased